2017
DOI: 10.1089/ten.tea.2016.0538
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Bioscaffolds as Immunomodulatory Biomaterials

Abstract: Suppression of the recipient immune response is a common component of tissue and organ transplantation strategies and has also been used as a method of mitigating the inflammatory and scar tissue response to many biomaterials. It is now recognized, however, that long-term functional tissue replacement not only benefits from an intact host immune response but also depends upon such a response. The present article reviews the limitations associated with the traditionally held view of avoiding the immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(67 citation statements)
references
References 91 publications
5
62
0
Order By: Relevance
“…These scaffolds have been associated with a robust but favourable host immune response that triggers constructive remodelling outcomes and an overall anti-inflammatory environment. In particular, macrophages have been recognized as a critical determinant of regeneration after injury, tissue remodelling and cross-talk with endogenous stem/progenitor cells 59 , 60 .…”
Section: Discussionmentioning
confidence: 99%
“…These scaffolds have been associated with a robust but favourable host immune response that triggers constructive remodelling outcomes and an overall anti-inflammatory environment. In particular, macrophages have been recognized as a critical determinant of regeneration after injury, tissue remodelling and cross-talk with endogenous stem/progenitor cells 59 , 60 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cells themselves manipulate their ECM microenvironment by synthesizing new matrix and modifying and digesting existing matrix, thereby altering its modulatory effects . ECM remodeling can expose previously hidden bioactive sequences or degrade intact bioactive sequences . Furthermore, digested soluble ECM fragments often modulate cell behavior in a manner that is distinct from the insoluble scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Given the role of the ECM in structural support of tissues, there has been significant effort in developing ECM‐based scaffolds for tissue engineering and regenerative medicine . For these applications, a biomaterial scaffold is often used to encourage the adhesion and infiltration of cells, and their differentiation and organization into functional tissues.…”
Section: Introductionmentioning
confidence: 99%
“…HAM has also been infiltrated by numerous leukocytes comprising macrophages. Recent studies have demonstrated that the extent of tissue regeneration after the implantation of a scaffold derived from the extracellular matrix depends on host tissue remodelling (Dziki, Huleihel, Scarritt, & Badylak, ). Macrophage polarization that plays an important role in this process can be dictated by the micro‐environment found in the scaffold, including cells (Brown, Valentin, Stewart‐Akers, McCabe, & Badylak, ).…”
Section: Discussionmentioning
confidence: 99%